Machining Performance with Respect to Cutting Forces, Vibrations, and Surface Quality in Drilling of Hybrid Abaca and Glass Fibers Reinforced Polymer Composite - Iqbal, Mohd; Firsa, Teuku; Nazaruddin, Nazaruddin; Nasution, Indera Sakti; Rizal, Muhammad; Qahhar, Jihadul; Hilmy, Irfan (IIUM Engineering Journal, 2025)
Initially, polymer composites utilized synthetic fibers as reinforcements due to their high strength and excellent water resistance. However, synthetic fibers are non-biodegradable, and their manufacturing process involves chemicals, rendering them environmentally unfriendly. Consequently, natural fibers began to be employed owing to their low production costs and inherent biodegradability. Nevertheless, natural fibers possess lower strength and non-uniform sizes, making them challenging to shape. Hybrid composites have been developed to address these limitations, combining synthetic and natural fibers to leverage their respective advantages and mitigate each other's shortcomings. As a result, hybrid composites are increasingly being adopted in various industries, including automotive, construction, sports, and electronics. During production, hybrid composite panels still require machining processes, such as milling to smooth the surface and drilling to create connecting holes, to become final products. Careful selection of machining parameters are needed to ensure product quality and minimize defects, including tool wear, fiber debonding, and delamination. Cutting forces and vibrations, critical factors influencing machining performance, can be regulated through optimized cutting conditions. This study examines the effects of cutting conditions on cutting forces and vibrations while drilling hybrid composites composed of abaca and glass fibers. Composite panels were fabricated using the compression molding method, consisting of 10% abaca fiber, 10% glass fiber, and 80% polyester resin with 1% hardener by weight. Drilling experiments were conducted using a two-flute high-speed steel (HSS) cutting tool under varying spindle speeds and feed rates. The results revealed that cutting parameters significantly influenced machining behaviour. Specifically, higher spindle speeds increased cutting forces by up to approximately 15%, whereas higher feed rates amplified vibration acceleration by up to 67.8%. These findings contribute to a deeper understanding of machining performance and provide valuable insights for optimizing drilling parameters to enhance machining efficiency and surface quality in hybrid natural–synthetic fiber composites. ABSTRAK: Pada mulanya, komposit polimer menggunakan serat sintetik sebagai penguat kerana kekuatannya yang tinggi dan rintangan air terbaik. Walau bagaimanapun, serat sintetik tidak terbiodegradasi, dan proses pembuatannya melibatkan bahan kimia, menjadikannya tidak mesra alam. Akibatnya, serat semula jadi mula digunakan kerana kos pengeluarannya yang rendah dan kebolehbiodegradan. Namun begitu, serat semulajadi mempunyai kekuatan lebih rendah dan saiz tidak seragam, menjadikannya sukar dibentuk. Bagi menangani masalah ini, komposit hibrid dibangunkan, menggabungkan serat sintetik dan semulajadi bagi memanfaatkan kelebihan masing-masing dan mengurangkan kelemahan masing-masing. Hasilnya, komposit hibrid semakin diterima pakai dalam pelbagai industri, termasuk automotif, pembinaan, sukan dan elektronik. Semasa peringkat pengeluaran, panel komposit hibrid masih memerlukan proses pemesinan, seperti milling bagi melicinkan permukaan dan penggerudian bagi mencipta lubang penyambung, sebelum menjadi produk akhir. Pemilihan parameter pemesinan yang teliti diperlukan bagi memastikan kualiti produk dan meminimumkan kecacatan, termasuk haus alat, nyah ikatan gentian dan penyimpangan. Daya pemotongan dan getaran, yang merupakan faktor kritikal mempengaruhi prestasi pemesinan, dapat dikawal melalui keadaan pemotongan yang optimum. Kajian ini mengkaji kesan keadaan pemotongan ke atas daya pemotongan dan getaran semasa penggerudian komposit hibrid yang terdiri daripada serat abaka dan gentian kaca. Panel komposit telah difabrikasi menggunakan kaedah pengacuan mampatan, yang terdiri daripada 10% gentian abaka, 10% gentian kaca, dan 80% resin poliester dengan 1% pengeras mengikut berat. Eksperimen penggerudian telah dijalankan menggunakan alat pemotong keluli berkelajuan tinggi (HSS) dua mata di bawah kelajuan dan kadar suapan berbeza. Dapatan menunjukkan bahawa parameter pemotongan mempengaruhi tingkah laku pemesinan dengan ketara. Khususnya, kelajuan lebih tinggi menyebabkan daya pemotongan meningkat sehingga kira-kira 15%, manakala kadar suapan lebih tinggi menguatkan pecutan getaran sehingga 67.8%. Penemuan ini menyumbang kepada pemahaman yang lebih mendalam tentang prestasi pemesinan dan menyumbang pandangan berharga dalam mengoptimum parameter penggerudian bagi meningkatkan kecekapan pemesinan dan kualiti permukaan komposit serat semulajadi-sintetik hibrid.